Effects of magnetic configuration on hot electrons in a minimum-B ECR plasma. (30th July 2020) - Li, J B; Li, L X; Bhaskar, B S; Toivanen, V; Tarvainen, O; Hitz, D; Li, L B; Lu, W; Koivisto, H; Thuillier, T; Guo, J W; Zhang, X Z; et al.
Abstract: To investigate the hot electron population and the appearance of kinetic instabilities in highly charged electron cyclotron resonance ion source (ECRIS), the axially emitted bremsstrahlung spectra and microwave bursts emitted from ECRIS plasma were synchronously measured on SECRAL-II (Superconducting ECR ion source with Advanced design in Lanzhou No. II) ion source with various magnetic field configurations. The experimental results show that when the ratio of the minimum field to the resonance field (i.e. Bmin /Becr ) is less than ∼0.8, the bremsstrahlung spectral temperature Ts increases linearly with the Bmin /Becr –ratio when the injection, extraction and radial mirror fields are kept constant. Above this threshold Ts saturates and the electron cyclotron instability appears simultaneously. This study has also demonstrated that Ts decreases linearly with the increase of the average gradient over the ECR surface when the on-axis gradient and hexapole field strengths are constant. In addition, it is found that Ts decreases with the increase of the gradient at the resonance zone ( ∇Becr on axis and < ∇Becr >) at relatively low mirror ratio and is insensitive to the gradient at high mirror ratio when Bmin is constant. Compared to a recent study taken on a fully superconducting ECRIS (Benitez et al 2017 IEEE Trans. Plasma Sci. 45 1746–54), in which it was concluded that Ts is only sensitive with Bmin, this article shows different results discussing the mechanisms behind the correlation of magnetic field parameters to Ts .